Lumbar Interbody Fusion: A Historical Overview and a Future Perspective. Issue 16 (August 2018) - de Kunder, Suzanne L.; Rijkers, Kim; Caelers, Inge J.M.H.; de Bie, Rob A.; Koehler, Peter J.; van Santbrink, Henk
Abstract : N/A: In this historical study we present an overview of lumbar interbody fusion surgery, which is one of the most commonly performed instrumented spinal fusion surgeries. The present article focuses on the history of lumbar interbody fusion surgery, starting from the foundation which was laid in the 19th and 20th century until today. The development of material and techniques evolved from simple wiring to the combination of transforaminal interbody fusion with polyether ether ketone cages and pedicle screw fixation with poly axial screws. The possibilities of instrumented spinal fusion grew during the past 100 years, and a considerable increase in instrumented spinal surgery was seen over the past decades. Today, gain lies in perfection of techniques and deliberate indication and development of guidelines. Therefore, more standardized studies on instrumented spinal surgery are needed to be done and techniques should be personalized on the patients' specific needs. Level of Evidence: N/A